Work Breakdown Structures Vs. Business Processes: An Investigation of Appropriate Method For Identifying The Number of Risks - Martdian Ratna Sari; Ronny Kountur; Bram Manuel; Adura Ahmad (Jurnal Aplikasi Bisnis dan Manajemen, 2025)
Background: Risk identification is a critical first step in the risk management process, laying the groundwork for subsequent stages like analysis, assessment, mitigation, and monitoring. Accurate identification is crucial to ensure that identified risks align with the company’s specific contextPurpose: This research aims to investigate how knowledge and understanding of various risk identification techniques influence the number of risk events identified by practitioners.Design/Methodology: An experimental approach was employed, involving 84 business school students. The study measured the dependent variable number of risks identified against independent variables comprising different risk identification approaches, both with and without context knowledge. Data analysis utilized the Chi-square technique of non-parametric statistics, maintaining a 95 percent confidence level.Findings: The findings reveal a significant correlation between the methods of identification approach (with or without knowledge of risk context) and the number of risks identified. Participants using the Business Process (BP) approach, regardless of context knowledge, identified more risks compared to those using the Work Breakdown Structure (WBS) approach or a No approach (NT).Conclusion: The findings highlight the importance of selecting appropriate risk identification methods and underscore the value of context knowledge in enhancing risk identification effectiveness. This research provides actionable insights for practitioners, analysts, and decision-makers actively engaged in risk management.Originality: This study contributes to the field by emphasizing the role of risk identification approaches and contextual knowledge, providing a framework for improving risk management practices. Keywords: risk identification, risk context, experiment approach, and risk knowledge